Of Disgust and Beauty (Jan Fabre) (Itinera, 2017)
The uniqueness of the work of Jan Fabre could be that disgust is always compensated by an appealing form. We shall see that Je suis sang and L’histoire des larmes exhibit the “exuberante liveliness” of human bodies in a sort of sacrificial fever, showing with no restraint, fluids and secretions of the body. If urine, sperm, sweat, and blood are generally considered as disgusting, on the contrary Jan Fabre does not worry about describing them as part of beauty. Then we could wonder if the purpose of the artist is not the destabilise … Apparently Jan Fabre wants to show the world as it is, with its part of disgust. While awaking our senses and therefore creating strong emotions, the artist probably expects to make possible a larger communication between us and the world.